Kääntäjäopiskelijoiden käsityksiä jälkieditoinnista - ”Se sotii niitä periaatteita vastaan, joita käännöskursseilla opetetaan” - Johanna Isosävi; Leena Salmi (Suomen kääntäjien ja tulkkien liitto, 2022)
This paper presents a study on translator students’ perceptions on post-editing. Students from
two different Master’s level courses were asked to post-edit machine translated texts and reflect
on the differences between light and full post-editing, on the differences between translating and
post-editing, on the role of error analysis and the use of the instructions given, as well as consider
their own aptitudes in post-editor. The results show that their attitudes were mainly
positive, but they felt that the task was challenging: leaving grammatical errors and “raw
translations” in the text were considered difficult. The majority of students also thought that
making a full post-editing was easier than making a light post-editing. This was also reflected in
their productions, as many students returned a light edit that corresponded to a full one.
Keywords: machine translation, post-editing, students’ reflections, translator, training